Sistem Pendukung Keputusan Pemilihan Peminatan Program Studi Teknik Informatika Menggunakan Metode SAW - Tinaliah Tinaliah; Triana Elizabeth (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2019)
Based on the Informatics Engineering study program curriculum, it can be seen that in the 5th semester students are required to take elective courses based on specialization provided. The purpose of specialization is for graduate students to have competencies that support them to continue their studies to a higher level (S2 or S3) and have work competencies that support them when they graduate from college. The problem is that it is difficult to determine the specialization that will be taken. Therefore, a decision support system is needed that can help STMIK XYZ Informatics Engineering students decide what they will choose. This decision support system applying Decission Fuzzy Multiple Attribute Making (FMADM) and Simple Additive weighting method (SAW). This decision support system design uses the Netbeans IDE 8.2 application and MySQL as the database